Surface Discharges and Flashover Voltages in Nanocomposite XLPE Samples - Papadakis, C.; Yin, Y.; Danikas, M.; Charalambous, C. (Engineering, Technology & Applied Science Research, 2018)
DC cable insulation is a field of intensive research activity. Special attention is being given to polymer nanocomposites, as promising insulation for such cables. Relatively little is known regarding surface discharges and flashover voltages for the aforementioned materials. In this paper, a comparison is made between samples of cross-linked polyethylene insulation with added MgO nanofillers and samples of pure polyethylene w.r.t. the behavior of surface discharges and flashover voltages in arrangements of water droplets of various conductivities on the said polymeric surfaces under the influence of uniform electric fields. Experimental evidence indicates that the flashover voltages of XLPE with MgO nanofillers are higher that the ones obtained with pure PE.